Improving Reading Comprehension in English: Tips & Strategies for Beginners - Rahmadillah, Suci; Wardani, Nia; Dega, Aries Bachtiar; Lubis, Yani (CV. PUSDIKRA MITRA JAYA, 2025)
This article examines effective strategies for improving reading comprehension in english, particularly for beginner learners. Reading comprehension is a fundamental skill that enables English language learners to acquire information and communicate effectively. The article highlights the challenges faced by beginner learners, such as limited vocabulary, difficulty with complex grammar, lack of background knowledge, and problems with inferring meaning. Through a literature review, the article identifies and categorizes various proposed and tested strategies to improve reading comprehension, highlighting their effectiveness and applicability in different educational contexts. The purpose of the article is to present how these strategies can be applied in the context of beginner learning. Findings indicate that interactive reading methods, vocabulary development, prior knowledge activation, and reading fluency training is profoundly influences reading comprehension and combination of these strategies can significantly improve reading comprehension skills, providing valuable insights for educators and learners, which in turn can improve their academic, professional, and social participation.